The Structural Features of α-Conotoxin Specifically Target Different Isoforms of Nicotinic Acetylcholine Receptors - Wu, Rui-Jie; Wang, Lei; Xiang, Hui (Current Topics in Medicinal Chemistry, 2016)
α-Conotoxins (α-Ctxs) are the major class of Ctxs extracted from the venom of marine cone snails. Most α-Ctxs specifically target various subtypes of the nicotinic acetylcholine receptors (nAChRs) with high affinity and potency as antagonists. Therefore, they may be used for the treatment of numerous diseases that nAChRs involved. The subtype affinity and selectivity of α-Ctxs arise from their amino acid composition and geometric conformation of microsites. To reveal the structural features of α-Ctxs, detailed structural information on the various nAChR subtypes and their ligand complexes is needed. This review article provides an overview of the structural data on α-Ctx-nAChR interactions to investigate the prediction and evaluation of the affinity and selectivity of α-Ctx.
Keywords: Structure-activity relationship